Information needs and seeking behaviour cf chemists: a comparative Study of Universities of Ibadan and llorin (2002)
This Study is conducted under a survey design. It attempts to identify the information needs and seeking behaviour of chemists in Universities of Ibadan and llorin. Descriptive research case study method was used to carry out the study. Data were collected by questionnaire administered to lecturers who were eligible to fill it in the departments of chemistry, biochemistry, geology, and pharmacy, or universities of Ibadan and llorin. In the two universities, the departmental lists of staff observed in the various departments concerned revealed that only 60 lecturers were qualified to be used in the research work. Out of the 60 questionnaires self-administered, 48 were well filed and returned. This represents 80% of the questionnaire given out. The findings of the research work showed that chemists need current research information. They prefer documented sources of information to non-documented sources. They were library literate making an extensive use of bibliographic tools in search of information. Chemists were not satisfied with the library resources and Services. Suggestions were made on how chemists can get the information they need on their own without solely depending on the library and the staff which they considered inefficient.